Predicted Versus Observed Major Adverse Cardiac Event Risk in Women With Evidence of Ischemia and No Obstructive Coronary Artery Disease: A Report From WISE (Women's Ischemia Syndrome Evaluation) - Tara Sedlak; Romana Herscovici; Galen Cook‐Wiens; Eileen Handberg; Janet Wei; Chrisandra Shufelt; Vera Bittner; Steven E. Reis; Nathaniel Reichek; Carl Pepine; C. Noel Bairey Merz (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Primary prevention risk scores are commonly used to predict cardiovascular (CVD) outcomes. The applicability of these scores in patients with evidence of myocardial ischemia but no obstructive coronary artery disease is unclear. Methods and Results Among 935 women with signs and symptoms of ischemia enrolled in WISE (Women's Ischemia Syndrome Evaluation), 567 had no obstructive coronary artery disease on angiography. Of these, 433 had had available risk data for 6 commonly used scores: Framingham Risk Score, Reynolds Risk Score, Adult Treatment Panel III, Atherosclerotic Cardiovascular Disease, Systematic Coronary Risk Evaluation, Cardiovascular Risk Score 2. Score‐specific CVD rates were assessed. For each score, we evaluated predicted versus observed event rates at 10‐year follow‐up using c statistic. Recalibration was done for 3 of the 6 scores. The 433 women had a mean age of 56.9±9.4 years, 82.5% were white, 52.7% had hypertension, 43.6% had dyslipidemia, and 16.9% had diabetes mellitus. The observed 10‐year score‐specific CVD rates varied between 5.54% (Systematic Coronary Risk Evaluation) to 28.87% (Framingham Risk Score), whereas predicted event rates varied from 1.86% (Systematic Coronary Risk Evaluation) to 6.99% (Cardiovascular Risk Score 2). The majority of scores showed moderate discrimination (c statistic 0.53 for Atherosclerotic Cardiovascular Disease and Systematic Coronary Risk Evaluation; 0.78 for Framingham Risk Score) and underestimated risk (statistical discordance −58% for Adult Treatment Panel III; −84% for Atherosclerotic Cardiovascular Disease). Recalibrated Reynolds Risk Score, Atherosclerotic Cardiovascular Disease, and Framingham Risk Score had improved performance, but significant underestimation remained. Conclusions Commonly used CVD risk scores fail to accurately predict CVD rates in women with ischemia and no obstructive coronary artery disease. These results emphasize the need for new risk assessment scores to reliably assess this population.